Agro-forestry in tropical Asia - Wijewardene, Ray (Pesquisa Agropecuaria Brasileira, 2014)
Traditionally the forest supplied tropical man's requirements of food, of fuel, and of fodder for his livestock. Increasing - largely immigrant - populations upon limited tropical land area, practiced in the open agriculture of a more tolerant environment, reduced fallowing periods and the time for natural regeneration of the forest soils. The resulting decline in yields and productivity was further aggravated through erosion caused by tropical rainfall upon soils bare-tilled to control weeds. The panacea of the high-inputs technology using (mainly) extemally sourced inputs could not be maintained; particularly in the context of rapidly increasing prices for the petroleum feedstock upon which most of these inputs and their transportation was based. Moreover, they failed to provide vital rural needs of fuel and fodder. The logical alternative, - now belatedly being researched, - is an accelleration of the time-proven practice of 'forest-fallow', through the creation of a simulated forest systematically and integrally linked into a sustainable (arable) farming system. The technique involves the planting in rows of rapid-growing (ideally NF) coppicing trees, with avenues two to five metres wide between the rows into which arable crops are seasonally planted with minimal tillage. The avenues are continually manured by the loppings from the rows of trees (hedges) which thus re-cycle leached fertility and nutrients stored in the sub-soil regions. The technique optimizes the alternating dry and wet seasons of the tropics for the rapid production of weed-shading and soil-cooling foliage during the dry season (otherwise unproductive in the temperate farming model) from the deeper reserves of moisture and nutrients available to the hedges. The wet season is then utilized for the growing of arable food crops in the fertile; leaf-mulched avenues between the lopped hedges. That at least one arable crop can continuously be grown in the avenues each year, with adequate yields and minimal external inputs, is now known. Research continues towards increasing productivity to two crops a year where a bimodal rainfall pattern might permit this. The technique is now also being researched in the populous regions, denuded of valuable forest, along the base of the Himalayas, with appropriate (NF) trees planted in hedge-rows along the ridges of the terraced fields. These provide the farmer with a continuous supply of fuelwood as well as foliage for fodder and mulch-fertility while also stabilizing bunds against erosion. Thus, the hitherto dry or winter seasons of this region are productively harnessed for the growing of produce vital to the economy of the farmer and his habitat, and complementary to the production of arable food corps in the terraced avenues between the bunds during the rainy summer months. The goal of a sustainable and productively integrated agro-forestry system for fuel and fodder as well as for food, with minimal (if any) involvement of extemally sourced inputs, is now within sight. Its management for optimal resource efficiency is now being researched.